O trânsito religioso e suas implicações na ação pastoral. - Oliveira, Everaldo José de (2021)
The general objective of the research is to investigate the influence of the Religious Transit on pastoral activity, identifying the problems that cause this transit and where the pastoral fits in this context, generating some possibilities for the resolution of such problems. The research questions started from the following specific objectives: to understand the mechanisms of the phenomenon of “religious transit”; Identify pastoral action in the context of “religious transit”; analyze the interrelationship of “religious transit” and what affects pastoral action. Our study was mainly linked to the theories of studies on modernity and postmodernity, and how these new times affect the life of the Catholic Church in Brazil. We raised discussion from authors like Sanchis (2018) and Berger (2017; 2018), with studies on syncretism, Vatican Council II, with researchers like Miranda (2000), Beozzo (1985) and Lamberigts; Routhier; Oliveira; Theobald (2017), as well as studies on pluralism and urban pastoral work by Brighenti (2000; 2010; 2011; 2015; 2018) and Libânio (1971; 1982; 2001, 2002; 2005). The universe of this work was the Religious Transit, understood by us as a current moment that enables the formation, mediation and maintenance of human consciousness. Thus, our focus was on the pastoral care of the Catholic Church and the faithful who circulate in this environment and the actions they take according to their spiritual needs. It is important to note that the Religious Transit allows access to a diverse religious universe, that is why we selected the data from the existing publications in articles, books and annals of events. Regarding the data generation process, the corpus was made up of information, possibly new or not, provided by the IBGE Census, which is used to guide various works on the Religious Transit. There were 32 digital articles, 5 printed magazines, 30 printed books, 2 digital books. The data were collected from May 2018 to March 2019. We could see that the Religious Transit thus formed has an impact on pastoralists by attracting or distancing the faithful from the Church and that certain religions are becoming a market religion to please and bring more and more followers into their practice. In the same way, the pastorals have a responsibility to find ways to enable the Church to resume activities to show the faithful that what matters is not their own desires but the will of God. In fact, all religious matrixes continue to manifest this will, after all, religion itself, which means to reconnect, must manifest God’s will through cults and rites. The church must lead its faithful to an experience with the living Christ that manifests itself through a true welcome. We characterize, thus, from the process of Religious Transit the pastorals and their influence, responsibility and action in the midst of this problem.